2019
DOI: 10.1200/jgo.18.00252
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness and Barriers to Seeking Medical Advice for Colorectal Cancer in the Gaza Strip: A Cross-Sectional Study

Abstract: PURPOSE Raising awareness of colorectal cancer (CRC) symptoms for early recognition, reduction of modifiable risk factors, and removing barriers to seeking medical help could lower its mortality. This study aimed to assess the level of public awareness of CRC in the Gaza Strip. MATERIALS AND METHODS This was a cross-sectional study conducted at three hospitals and 10 high schools between September and October 2017. The Arabic version of the validated Bowel Cancer Awareness Measure (BoCAM) questionnaire was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 28 publications
6
31
0
Order By: Relevance
“…In concordance with other studies, knowledge of cancer risk factors as well as signs and symptoms improved with age [10,11,[22][23][24][25]. This is not surprising as informal learning through experiences in life and exposure to [2].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In concordance with other studies, knowledge of cancer risk factors as well as signs and symptoms improved with age [10,11,[22][23][24][25]. This is not surprising as informal learning through experiences in life and exposure to [2].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, reducing barriers for first presentation is as important as improving knowledge and awareness of cancer symptoms [9,[32][33][34][35]. Barriers can be emotional, like being worried about possible results, embarrassment or fear to see a n number of participants tested doctor, service-related such as difficulty getting an appointment with a doctor, or practical like being too busy to see a doctor or difficulty with arranging transport [9][10][11]. However, negative beliefs also have a strong impact, such as the conviction that there is no cure for cancer or the treatment is worse than the actual disease [23,32,33,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies conducted in the Gaza Strip showed low awareness of symptoms as well as risk factors for both BC and CRC [10,11]. Some educational initiatives were held by local universities and institutions.…”
Section: Introductionmentioning
confidence: 99%